Organic Lettuce Growth And Nutrient Uptake Response To Lime, Compost And Rock Phosphate - Brito, Luís Miguel (2018)
Fertilizer recommendations are needed to increase organic vegetable yields. Thus, organic lettuce growth and nutrient uptake was investigated in a randomized block pot experiment with twelve treatments from the factorial structure of three factors: (i) Gafsa phosphate [0 and 200 kg phosphorus pentoxide (P 2 O 5 ) ha -1 ], (ii) compost from source separated municipal organic waste (0, 15, and 30 t ha -1 ) and (iii) limestone [0 and 8 t ha -1 calcium carbonate (CaCO 3 ) equivalent]. Lettuce yield increased with compost application and a first order interaction between lime and phosphate was clear because lime partially replaced the need for phosphate. This was explained by the effect of liming on P availability in acid soils. Nitrogen (N), phosphorus (P), and potassium (K) accumulation increased in lettuces produced with compost or phosphate but only the accumulation of N was increased with lime. This compost is recommended to increase nutrient availability for organic lettuce whereas the need for phosphate fertilization may decrease with liming.